Teachers' Innovative Strategies in Integrating LMS for Practical Learning: A Case Study in Vocational High Schools - Suparmin; Suharno; Sukatiman (LPPM Undiksha, 2025)
Limited practical tools are a crucial obstacle in vocational education because they disrupt the continuity of skills learning, which should be hands-on and contextual. The imbalance between the number of students and practical tools results in unproductive waiting time and low learning effectiveness. This study aims to examine teachers' strategies in integrating a Learning Management System (LMS) as a complementary medium for practical learning, and to understand students' experiences in this process. Using a qualitative approach with an intrinsic case study design, data were collected through in-depth interviews, field observations, and documentation studies, with participants consisting of three practicing teachers and eight students from the Light Vehicle Engineering program. The results show that the LMS Moodle was adopted as an adaptive response to the limited practical tools. Teachers utilized this platform to embed video tutorials, assign case studies, and divide digital-practice groups, rotating. Students demonstrated increased learning independence and engagement, despite facing technical challenges. This study recommends an LMS integration model to complement direct practice, involving visual tutorial components, asynchronous feedback, and flexible, rotation-based learning. These findings contribute to developing technology-based practical learning in vocational high schools (SMKs) experiencing limited facilities, while expanding the literature on digital adaptation in context-based vocational education.